The onset of visual experience gates auditory cortex critical periods - Todd M. Mowery (Nature Portfolio, 2016)
Visual and auditory systems influence each other during development. Here, the authors show that the onset of eyelid opening regulates critical points during which the auditory cortex is sensitive to hearing loss or the restoration of hearing